The 4Ps: Developing a capabilities approach to mobility justice in the context of skilled migration - Thomas-Maude J (Taylor and Francis Group, 2026)
This article advances a capabilities approach to mobility justice by introducing an operational conceptual tool, the 4Ps, comprising the professional, (inter)personal, and practical aspects of mobilities and capabilities, interwoven with power regimes. Drawing on a mixed methods study of international medical graduates (IMGs) in Aotearoa New Zealand, the paper explores how recognition, exclusion, and institutional power regimes shape migrant professionals' ability to convert their knowledge, skills, and qualifications into meaningful opportunities. The 4Ps emerged from the intersection of mobility justice and capabilities theory, and were iteratively developed through empirical engagement with the lived realities of IMGs navigating medical registration. This approach emphasises the context-dependent and relational nature of (in)justice, recognising how personal, social, and systemic conversion factors constrain or enable mobilities and capabilities. Situating these dynamics in the unique postcolonial context of Aotearoa New Zealand, the paper demonstrates how a capabilities approach to mobility justice can account for the complexity of skilled migration, including both the human and more-than-human elements of professional recognition across borders. While empirically grounded, the framework offers broader relevance for skilled migration research, contributing a transferable lens and a set of analytic prompts for exploring how mobilities, recognition, and capability conversion interact across transnational professional contexts.